Oviposition of Panonychus ulmi (Koch, 1936) (Acari: Tetranychidae) in response of conspecific and heterospecific mites cues - Rode, Priscila de A.; Schneider, Julia R.; Ferla, Noeli J. (Entomological Communications, 2024)
This study aimed to assess oviposition of Panonychus ulmi (Koch, 1936) (Acari: Tetranychidae) in response of conspecific and heterospecific mites cues on apple trees (Malus domestica Borkh: Rosaceae). The oviposition of P. ulmi was measured on apple tree leaves with the presence of webs, eggs, and other cues of phytophagous mites (Aculus schlechtendali (Nalepa, 1890) (Acari: Eriophyidae), P. ulmi, Tetranychus urticae Koch, 1936 (Acari: Tetranychidae), and Tetranychus ludeni Zacher, 1913 (Acari: Tetranychidae)). The presence of conspecific webs and cues increased the oviposition of P. ulmi, while the presence of A. schlechtendali and T. urticae webs and eggs and A. schlechtendali cues decreased oviposition. The oviposition increases in the presence of conspecifics suggesting that P. ulmi performs better in environments without heterospecific mites. On the other hand, the P. ulmi decreases in oviposition in presence of heterospecific mite cues suggesting a potential competitive displacement of tetranychid by eriophyid mites.